1235 Development And Validation of a Scale to Assess Knowledge of Outcomes Following Preterm Birth. (October 2012) - Henderson, D; Beer, C; Wolke, D; Johnson, S
Abstract : Background and Aims: Preterm children are at high-risk for special educational needs. Education professionals' (EPs) knowledge of health conditions is crucial for providing appropriate support, however no studies have investigated their knowledge in this area. To facilitate such research we developed a scale to assess knowledge of outcomes following preterm birth. Methods: Following a comprehensive literature review, 35 forced choice (true/false/don't know) items were developed to assess knowledge of neurodevelopmental and educational outcomes. Item scores were summed to provide a total knowledge score (range 0–35). The scale was completed by 120 EPs and 70 experts in the field (neonatologists/paediatricians). Results: EPs' responses revealed floor effects for 2 items which were removed. The remaining 33-item scale had excellent internal reliability (Cronbach's Alpha=0.82). EPs' knowledge scores were normally distributed (Mean 11.3; SD 5.4) and differed significantly by level of training (F(3, 111)=2.78, p=0.045) indicating construct validity. Experts' knowledge scores were not normally distributed (Median 26.5; IQR 23.0–29.0) and were significantly higher than EPs (p<0.001) indicating discriminative validity. Principal components factor analysis revealed two factors: developmental problems, internalising difficulties and attainment, need for additional support in the classroom. EPs' scores were significantly lower than experts on both sub-scales. Conclusions: This short scale has good psychometric properties and provides a useful tool for teaching and assessing clinical and education professionals' knowledge of preterm birth. Study results revealed the need to improve EPs' knowledge of sequelae of prematurity if they are to support increasing numbers of preterm children in the classroom.